Patterns, Drivers, and Ecological Implications of Upwelling in Coral Reef Habitats of the Southern Red Sea. Issue 2 (5th February 2021) - DeCarlo, Thomas M.; Carvalho, Susana; Gajdzik, Laura; Hardenstine, Royale S.; Tanabe, Lyndsey K.; Villalobos, Rodrigo; Berumen, Michael L.
Abstract: Coral reef ecosystems are highly sensitive to thermal anomalies, making them vulnerable to ongoing global warming. Yet, a variety of cooling mechanisms, such as upwelling, can offer some respite to certain reefs. The Farasan Banks in the southern Red Sea is home to hundreds of coral reefs covering 16, 000 km 2 and experiences among the highest water temperatures of any coral‐reef region despite exposure to summertime upwelling. We deployed an array of temperature loggers on coral reefs in the Farasan Banks, enabling us to evaluate the skill of satellite‐based sea surface temperature (SST) products for capturing patterns of upwelling. Additionally, we used remote sensing products to investigate the physical drivers of upwelling, and to better understand how upwelling modulates summertime heat stress on coral communities. Our results show that various satellite SST products underestimate reef‐water temperatures but differ in their ability to capture the spatial and temporal dynamics of upwelling. Monsoon winds from June to September drive the upwelling in the southern Red Sea via Ekman transport of surface waters off the shelf, and this process is ultimately controlled by the southwest Indian monsoon in the Arabian Sea. Further, the timing of the cessation of monsoon winds regulates the maximum water temperatures that are reached in September and October. In addition to describing the patterns and mechanisms of upwelling, we discuss the potential ecological implications of this upwelling system, including modulation of coral bleaching events and effects on biodiversity, sea turtle reproduction, fish pelagic larval duration, and planktivore populations. Plain Language Summary: Winds blowing parallel to a coastline can push the surface layer of the ocean away from shore, thereby pulling up deeper, cooler water in a process called "upwelling". In the Red Sea, an elongated body of water between Africa and the Arabian Peninsula, persistent along‐shore winds cause upwelling on shallow‐water coral reefs. This process is detectable from satellites orbiting the earth that measure the temperature of the sea surface, but substantial differences exist in the data provided by these satellites. We show which satellites are best suited for characterizing the patterns of upwelling in the Red Sea across time and space by comparing them to an array of temperature loggers deployed underwater, and we show how upwelling in the Red Sea is ultimately driven by larger‐scale wind patterns in the Indian Ocean. Additionally, our results shed light on how upwelling affects marine life in the Red Sea. For example, if temperatures become too high, corals are prone to "bleach" and die, while sea turtle hatchlings become mostly female. Although upwelling of cooler water may help alleviate these stresses, it may also have negative consequences for some organisms due to higher nutrient concentrations in the deeper, upwelling water. Key Points: In the southern Red Sea, wind‐driven upwelling in coral reef habitats is regulated by remote forcing from the southwest Indian Monsoon The skill of capturing the spatial and temporal patterns of upwelling varies among satellite‐based sea surface temperature products Upwelling dampens southern Red Sea maximum temperatures by 1–3°C, with important consequences for corals, sea turtles, and biodiversity